MEMBANGUN DESA UNTUK INDONESIA MAJU - Br Sembiring, Ribka Kariani; Ambarwati, Nova Florentina; Gulo, Inne Kristina; Gregorius, Binsar; Br Saragih, Marpaung Artianna Christin (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
This community service was conducted in Penampen Village, Karo Regency, as part of the implementation of the Community Service Program (KKN) for the KKN course, accompanied by field supervising lecturers. This article aims to explore sustainable village development strategies to achieve Indonesia's advancement. By involving the community in the development process, it can become a driving force for national economic growth. The activities focus on enhancing local residents' skills and education. By involving the community in training and educational programs, it helps them acquire new knowledge that can improve their living standards. Teaching basic technology skills opens up new job opportunities or increases efficiency in daily work. Introducing technology to children at the elementary, middle, and high school levels is an important step in preparing students to face future challenges. The community's enthusiasm is evident from their active participation, both in material and non-material support. This shows that the programs implemented are relevant to their needs and can foster a sense of ownership towards the program. Good cooperation between KKN members and the village community is key to the success of this program. This synergy creates a conducive environment for learning and growing together. With all these activities, it is clear that the KKN program not only provides short-term benefits but also has the potential to bring long-term positive changes to the village.